Synthesis of N-Phenylcarbamate by C–N Coupling Reaction without Metal Participation - Ji, Long; Ablajan, Keyume (Synthesis, 2023)
We have developed a new method for the synthesis of carbamates from amine and hydrazine formate. The reaction occurs in the presence of iodine and tert-butyl hydroperoxide, in which carbazates are produced via alkoxycarbonyl radical formation for cross-coupling reaction. The method exhibits broad functional group tolerance and affords a series of N-phenylcarbamates in moderate to good yields. Remarkably, our approach is metal free and utilizes cheap, readily available raw materials and relatively universal substrates.
Keywords: metal-free C–N coupling; one-pot synthesis; mild conditions